Mapping Kesiapan Wajib Pajak terhadap Berakhirnya Penggunaan Peraturan Pemerintah No 23 Tahun 2018 - Mertawan, Made Adi Guna; Darma, Gede Sri (E-Jurnal Akuntansi; Vol 31 No 9 (2021)DO - 10.24843/EJA.2021.v31.i09.p08, 2021)
This study aims to determine the extent of the readiness of taxpayers in the transition to the use of government regulation no. 23 of 2018 (PP 23/2018) towards the use of tariffs in Article 17 of the Income Tax Law (UU PPh). The purpose of issuing PP 23/2018 is the government's policy in simplifying taxpayers in carrying out tax administration, but PP 23/2018 can not always be applied but there is a limited period of use as a form of taxpayer learning taxpayers to improve taxpayer compliance. The research sample was determined by snowball and purposive sampling, namely taxpayers in the form of limited shares with data obtained from observations, interviews and documentation. The data analysis technique used is the Miles and Hubberman qualitative analysis technique. The results of the study indicate that taxpayers have understood in carrying out bookkeeping but understanding of Article 17 of the Income Tax Law is still low, taxpayers have not received information about the time limit for using PP 23/2018. Keywords: PP 23/2018; Bookkeeping; Article 17 of the Income Tax Law.